The CLK inhibitor SM08502 induces anti-tumor activity and reduces Wnt pathway gene expression in gastrointestinal cancer models - Tam, Betty Y.; Chiu, Kevin; Chung, Heekyung; Bossard, Carine; Nguyen, John Duc; Creger, Emily; Eastman, Brian W.; Mak, Chi Ching; Ibanez, Maureen; Ghias, Abdullah; Cahiwat, Joseph; Do, Long; et al. (Cancer letters, 2020)
The Wnt/β-catenin signaling pathway is aberrantly activated in colorectal (CRC) and many other cancers, and novel strategies for effectively targeting it may be needed due to its complexity. In this report, SM08502, a novel small molecule in clinical development for the treatment of solid tumors, was shown to reduce Wnt pathway signaling and gene expression through potent inhibition of CDC-like kinase (CLK) activity. SM08502 inhibited serine and arginine rich splicing factor (SRSF) phosphorylation and disrupted spliceosome activity, which was associated with inhibition of Wnt pathway-related gene and protein expression. Additionally, SM08502 induced the generation of splicing variants of Wnt pathway genes, suggesting that its mechanism for inhibition of gene expression includes effects on alternative splicing. Orally administered SM08502 significantly inhibited growth of gastrointestinal tumors and decreased SRSF phosphorylation and Wnt pathway gene expression in xenograft mouse models. These data implicate CLKs in the regulation of Wnt signaling and represent a novel strategy for inhibiting Wnt pathway gene expression in cancers. SM08502 is a first-in-class CLK inhibitor being investigated in a Phase 1 clinical trial for subjects with advanced solid tumors (NCT03355066). •SM08502 is a potent small-molecule CDC-like kinase (CLK) inhibitor.•SM08502 inhibited the Wnt signaling pathway in vitro and in vivo in colorectal cancer models.•SM08502 affected alternative splicing, which underlies inhibition of aberrant Wnt signaling.•SM08502 demonstrated potent anti-tumor activity in xenograft models of GI cancer.